2018
DOI: 10.1590/1413-785220182601175203
|View full text |Cite
|
Sign up to set email alerts
|

Two Classifications for Surgical Wound Hematoma After Total Hip Replacement

Abstract: Objective:To determine the reliability of two classification methods for wound hematoma after total hip replacement. Methods:This prospective cohort study was conducted on patients who underwent total hip replacement for hip osteoarthritis between May 2014 and April 2015. Epidemiological, surgical, and functional data were assessed. Two experienced hip surgeons evaluated 75 pictures of wounds taken 24 hours after surgery. Both evaluators performed the analysis twice, with a 6-week interval between the two anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A postoperative hematoma is a possible complication after THA [ 2 , 3 ]. Although uncommon, this complication can have substantial consequences, such as persistent wound drainage and infection [ 2 , 4 ]. Using NSQIP, our study aimed to identify the incidence, predictors, and the subsequent associated clinical complications of postoperative hematomas requiring reoperation after primary THA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A postoperative hematoma is a possible complication after THA [ 2 , 3 ]. Although uncommon, this complication can have substantial consequences, such as persistent wound drainage and infection [ 2 , 4 ]. Using NSQIP, our study aimed to identify the incidence, predictors, and the subsequent associated clinical complications of postoperative hematomas requiring reoperation after primary THA.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study found that 0.41% of patients required surgical intervention to treat postoperative hematoma after primary THA [ 3 ]. Although rare, this complication can be catastrophic, resulting in persistent wound drainage, excessive pain, neurological impairment, infection, and even death [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In studying factors related to a haematoma, we consider the US technique likely a strength so that we could carefully detect the presence and size of haematoma, thus overcoming the clinical disagreement between surgeons. In addition, the comprehensive geriatric assessment could be an additional study’s strength, offering the possibility to explore the role of non canonical factors potentially involved in the development of haematoma, despite biological plausibility [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future technology will likely become more common to help diagnose a POFC. Fagotti et al 71 studied the reliability of two hematoma classification systems in THA. Their objective classification systems, which employed a dedicated computer algorithm, demonstrated improved accuracy in classifying the severity of hematomas in arthroplasty.…”
Section: Discussionmentioning
confidence: 99%